2022
DOI: 10.4014/jmb.2111.11003
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinted GelMA/PEGDA Hybrid Scaffold for Establishing an In Vitro Model of Melanoma

Abstract: PEGDA composite scaffolds that mimic the microenvironment of human malignant melanoma cell (A375) growth and construct in vitro melanoma micro-models. The GelMA/PEGDA hybrid scaffold was tested by the mechanical property, cell live/dead assay, cell proliferation assay, cytoskeleton staining and drug loading assay. The growth of tumor cells in two-and three-dimensional culture systems and the anti-cancer effect of luteolin were evaluated using the live/dead staining method and the Cell Counting Kit-8 (CCK-8) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Similar spheroid morphology was also found for A375 cells cultured in alginate-based hydrogel, 48 liquid-overlay method, 49 and other GelMA-based scaffolds. 50 The spheroid formation bigger than 500 μm could cause limited diffusion of oxygen and nutrients to cells, resulting in populations of proliferative, quiescent, and necrotic cells. 51,52 However, the cell necrosis was not observed in this study based on the continues cellular proliferation and upregulation of Ki67 gene expression from Day 5 to Day 7, which may since the cellular spheroid size did not reach 500 μm at Day 5, and longer culture time, like 10−15 days may be needed to observe the cellular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar spheroid morphology was also found for A375 cells cultured in alginate-based hydrogel, 48 liquid-overlay method, 49 and other GelMA-based scaffolds. 50 The spheroid formation bigger than 500 μm could cause limited diffusion of oxygen and nutrients to cells, resulting in populations of proliferative, quiescent, and necrotic cells. 51,52 However, the cell necrosis was not observed in this study based on the continues cellular proliferation and upregulation of Ki67 gene expression from Day 5 to Day 7, which may since the cellular spheroid size did not reach 500 μm at Day 5, and longer culture time, like 10−15 days may be needed to observe the cellular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained were validated using a mouse xenograft model and it was found that the 3D in vitro method helps in the understanding of tumorigenesis and the associated tumor micro-environment [136]. A 3D bioprinted GelMA/PEGDA hybrid scaffold mimicked the tumor micro-environment of human malignant melanoma cell and was reported to be suitable for the expansion and differentiation of tumor cells; additionally, tumor cells were growing faster and exhibited drug-resistant potential [137]. Alginate and gelatin bioprintable hydrogel together with BC cells and fibroblast were printed to form a 3D mimicking tumor micro-environment.…”
Section: Tumor Microenvironment and 3d Printingmentioning
confidence: 94%
“…used 3D bioprinting to construct GelMA-polyethylene (glycol) diacrylate composite scaffolds for human malignant melanoma cell growth. The results showed a high aggregation, expansion and differentiation of melanoma cells on the bioprinted scaffolds [ 160 ]. Similarly, Jeong et al .…”
Section: Applications Of 3d Skin Bioprintingmentioning
confidence: 99%